Gambaran Dispepsia pada Pasien Rawat Inap di Rumah Sakit Harapan Sehat pada tahun 2022 - Adico Notareza Aulia; Laila Apriani Hasanah Harahap; Ilum Anam (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Dyspepsia is still the most common problem at every age. It causes discomfort in the stomach, nausea, vomiting and other complaints. Dyspepsia can also interfere with a person's life, causing the sufferer to have to rest or be hospitalized.This research was conducted at the Harapan Sehat private hospital in Meulaboh, West Aceh.This study uses a descriptive method, where data is taken based on the medical records of patients hospitalized at Harapan Sehat hospital throughout 2022. The data taken were patients diagnosed with dyspepsia and treated by an internal medicine specialist.In this study, 256 patients were admitted with a diagnosis of dyspepsia by an internal medicine doctor.The study found that dyspepsia cases were mostly experienced by women, with ages above 40 to 60 years old being the most common age. Meanwhile, patients underwent the most treatment period of 3 days.